(untitled) (AYUSHDHARA, 2017)
Integrative medicine means combined work of various experts of various disciplines to create a holistic effect. Human is a combination of body, mind and soul. All three aspects of human should be cared and cured by healthcare systems.Body and mind are connected to each other. Physical problems create mental problems and mental problems create physical problems. There is a psychosomatic mechanism. Apart from modern medicine, Ayurved, Homeopath, Unani, Yoga and Naturopathy are popular healthcare systems in the society. Any one system is not sufficient to provide health and healing to all in all diseases. In modern medicine, there are several adverse effects of antibiotics and analgesics. World is looking towards Ayurved and homeopath, etc. for safe medicines. Now, it is great responsibility of various research councils like CCRAS, CCH, etc. to invent new drugs to cure new diseases.Interdisciplinary seminars are essential to exchange results find out by these research councils. Healthcare system in rural areas is very poor. This can be improved by using technology. Advanced and specialized healthcare can be provided in rural areas by Tele Ayush system. Ministry of Ayush has done many works for globalization of Ayurved but the ministry has to do many works now for upgradation of Ayurved in India and abroad.